The effect of SOX4 gene 3′UTR polymorphisms on osteoporosis - Li, Guo; Gu, Zuchao; He, Yue; Wang, Chongwen; Duan, JiQiang (Journal of orthopaedic surgery and research, 2021)
Objective This study aimed to explore the correlation between the SRY-related high-mobility-group box gene 4 (SOX4) 3′ untranslated region (UTR) single nucleotide polymorphism (SNP) and osteoporosis susceptibility. Methods The study recruited 330 osteoporosis patients (the case group) and 330 non-osteoporosis patients (the control group) in Sichuan Chengdu First People’s Hospital and Zibo Central Hospital from August 2016 to August 2019. Sanger sequencing was used to analyze the genotypes of SOX4 gene rs79958549, rs139085828, and rs201335371 loci. Multi-factor dimensionality reduction (MDR) was used to analyze the interaction between the SOX4 gene rs79958549, rs139085828, and rs201335371 loci and the clinical characteristics of the subjects. Results The risk of osteoporosis in the carriers of A allele at SOX4 rs79958549 was 5.40 times that in the carriers of the G allele (95% CI 3.25–8.96, P < 0.01). The risk of osteoporosis in the carriers of the A allele at SOX4 rs139085828 was 1.68 times that in the carriers of the G allele (95% CI 1.45–1.85, P < 0.01). The risk of osteoporosis in the carriers of the T allele at SOX4 rs201335371 was 0.54 times that in the carriers of the C allele (95% CI 0.43–0.69, P < 0.01). The SOX4 gene rs79958549, rs139085828, and rs201335371 A-A-C haplotype (OR = 5.14, 95% CI 2.45–10.57, P < 0.01) were associated with increased risk of osteoporosis and G-G-T haplotype was significantly associated with decreased risk of osteoporosis (OR = 0.48, 95% CI 0.38–0.62, P < 0.01). The interaction among the factors of sex, smoking, drinking, rs79958549, rs201335371 was the best model for osteoporosis prediction, and the risk for osteoporosis in ‘high-risk combination’ was 2.74 times that of ‘low-risk combination’ (95% CI 1.01–7.43, P = 0.04). Multiple logistic regression analysis revealed that the risk factors for osteoporosis were BMD (OR = 5.85, 95% CI 2.88–8.94, P < 0.01), T score (OR = 8.54, 95% CI 5.66–10.49, P < 0.01), Z score (OR = 3.77, 95% CI 2.15–8.50, P < 0.01), rs79958549 SNP (OR = 6.92, 95% CI 3.58–8.93, P < 0.01), and rs139085828 SNP (OR = 2.36, 95% CI 1.85–4.27, P < 0.01). The protective factor for osteoporosis was rs201335371SNP (OR = 0.48, 95% CI 0.32–0.75, P < 0.01). Conclusion The SOX4 gene SNPs rs79958549, rs139085828, and rs201335371 loci were significantly associated with osteoporosis risk.